Sustainability Risk and Supply Chain Performance: Role of Risk Mitigation Capability and Supply Chain Management - Dr. Khaled A. Al Falah; Dr. Veera Pandiyan Kaliani Sundram (Decision Making: Applications in Management and Engineering, 2025)
The research aimed to examine the impact of sustainable risks on supply chain performance with the mediating effect of risk mitigation in food companies. The study also tested the moderating influence of supply chain management. Quantitative data through self-administered surveys were collected from 282 employees using a convenient sampling technique. Smart PLS used for inferential statistics, and SPSS is used for demographics. The study results show that economic, social, and environmental risks have a significant impact on supply chain performance. Further mediating effect results also show that risk mitigation partially mediates among all sustainability risk factors and supply chain performance. Supply chain management also significantly moderates between sustainable risk factors and risk mitigation strategies. These study findings showed that sustainable risk factors contributed to increasing the supply chain performance when they are properly managed. The study results also contributed a significant role in risk mitigation as a bridge to improve the supply chain performance. The research also uncovers the significant moderating effect of supply chain management in strengthening the relationship between sustainability risks and mitigation efforts. In order to achieve resilient and sustainable supply chain performance, food firms can benefit greatly from these insights